Harnessing Workforce Diversity for Enhanced Employee Performance: Strategic Insights for Capacity Building - Anthony, Katherine D.; Trajico, Kathleen D. (Future Science / FSH-PH Publications, 2024)
Diversity, a consequence of evolution and globalization, has prompted businesses to reevaluate their organizational structures. This shift has created opportunities for management to harness the valuable perspectives and ideas of diverse employees, which serve as catalysts for success in the intricate and ever-changing business environment. Consequently, the primary objective of this study is to investigate the relationship between employees' perceptions of diversity practices within the organization and their influence on employee productivity, engagement, and performance. Furthermore, the study seeks to ex-plore effective strategies for managing workforce diversity. The ma-jority of respondents belong to the age group of 41 years and above, are female, and are Tagalog employees. Respondents unanimously acknowledged that various diversity practices have a positive impact on employee productivity and overall organizational performance. However, significant organizational challenges such as resistance to change, communication barriers, and resource constraints hinder the successful implementation of diversity programs and, consequently, employee performance. However, there was no significant variation in the influence of diversity practices on employee productivity and overall performance across demographic groupings, such as age, gen-der, and ethnicity. The most effective diversity integration strategies employed within the organization involved regular diversity training programs and the involvement of all employees in diversity initia-tives. Furthermore, integrating diversity into employee performance leads to heightened employee satisfaction and a sense of belonging. Employees become more proactive in their roles when they feel in-cluded and valued within the organizational culture, resulting in ele-vated employee engagement levels in organizations that actively sup-port and promote diversity and inclusion. Furthermore, the integra-tion of diversity in employee engagement leads to diverse perspec-tives that contribute to improved decision-making and enhanced work outputs. The measurement and evaluation framework developed by the U.S. Agency for International Development (USAID) for Diversity Management has been adapted to assess the impact of diversity initiatives on employee performance. The three-module training program was designed to help small busi-nesses develop inclusive cultures and enabling work environments as well as strategies for bringing in, managing, and retaining a diverse workforce.